Intake of Red Wine Increases the Number and Functional Capacity of Circulating Endothelial Progenitor Cells by Enhancing Nitric Oxide Bioavailability - Huang, Po-Hsun; Chen, Yung-Hsiang; Tsai, Hsiao-Ya; Chen, Jia-Shiong; Wu, Tao-Cheng; Lin, Feng-Yen; Sata, Masataka; Chen, Jaw-Wen; Lin, Shing-Jong (Arteriosclerosis, thrombosis, and vascular biology, 2010)
OBJECTIVE—Red wine (RW) consumption has been associated with a reduction of cardiovascular events, but limited data are available on potential mediating mechanisms. This study tested the hypothesis that intake of RW may promote the circulating endothelial progenitor cell (EPC) level and function through enhancement of nitric oxide bioavailability. METHODS AND RESULTS—Eighty healthy, young subjects were randomized and assigned to consume water (100 mL), RW (100 mL), beer (250 mL), or vodka (30 mL) daily for 3 weeks. Flow cytometry was used to quantify circulating EPC numbers, and in vitro assays were used to evaluate EPC functions. After RW ingestion, endothelial function determined by flow-mediated vasodilation was significantly enhanced; however, it remained unchanged after water, beer, or vodka intake. There were significantly increased numbers of circulating EPC (defined as KDRCD133, CD34CD133, CD34KDR) and EPC colony-forming units only in the RW group (all P<0.05). Only RW ingestion significantly enhanced plasma levels of nitric oxide and decreased asymmetrical dimethylarginine (both P<0.01). Incubation of EPC with RW (but not beer or ethanol) and resveratrol in vitro attenuated tumor necrosis factor-α–induced EPC senescence and improved tumor necrosis factor-α–suppressed EPC functions and tube formation. Incubation with nitric oxide donor sodium nitroprusside significantly ameliorated the inhibition of tumor necrosis factor-α on EPC proliferation, but incubation with endothelial nitric oxide synthase inhibitor l-NAME and PI3K inhibitor markedly attenuated the effect of RW on EPC proliferation. CONCLUSION—The intake of RW significantly enhanced circulating EPC levels and improved EPC functions by modifying nitric oxide bioavailability. These findings may help explain the beneficial effects of RW on the cardiovascular system. This study demonstrated that a moderate intake of RW can enhance circulating levels of EPC in healthy subjects by increasing nitric oxide availability. Direct incubation of EPC with RW and resveratrol can modify the functions of EPC, including attenuation of senescence and promotion of EPC adhesion, migration, and tube formation. These data suggest that RW ingestion may alter the biology of EPC, and these alterations may contribute to its unique cardiovascular-protective effect.